Repositioning of Islamic Economics in the Era of Globalization from the Maqāṣid Syarī’ah Perspective - Asyharul Muala (Journal of Islamic Law)
Economic globalization has become a major stream for the past two to three decades. A multi-dimensional process that demands consistency and integration with all fields in the fields of economy, politics, social, culture, and ideology. The dominance of economic globalization gets stronger since the establishment of the General Agreement on Tariff and Trade (GATT) in the early 1990s. By claiming a noble aim, economic globalization is supported by ideologies that are often considered biased, namely capitalism and liberalism. Capitalism, a winning ideology and has successfully surpassed socialist-communists, remains incomplete as an economic ideology. In this ideology, profits revolve only around particular people; yet, others become exploited victims. This qualitative research presents solutions to global economic problems. Islam, with its sharia economic concept, appears at the right time. Islamic economics is an alternative to answer economic issues. The purpose of the economy itself is not only in the fulfillment of individual needs but also in the creation of mutual benefits. The concepts proposed by Islamic economics is in accordance with maqāṣid syarī'ah, which is to fulfill five basic problems (al-darūriyat al-khams). Thus, those basic needs are fulfilled for the sake of maintaining religion, soul, mind, lineage and human property. To achieve these objectives, some steps need to be taken in implementing Islamic economics, namely, reviving humanity factors, reducing wealth concentration, restructuring current economic, and restructuring current financial conditions.